Nilai-Nilai Budaya dalam Novel Batu Manikam Karya Bernard Batubara dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia di SMA - Mery Nurfa Dilla; Afnita Afnita (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The emergence of literary works is not solely written to provide entertainment to readers, but this is also a means of instilling cultural values ​​in the lives of readers. The presence of cultural values ​​in a literary work aims to provide positive values ​​in people's lives which will become a human guide in behaving. In addition, this cultural value will be a driving factor for a good way of thinking in society. This study aims to analyze cultural values ​​in one of Bernard Batubara's novels because the novel contains many life values, especially cultural values. This research is a type of library research. The data in this study is in the form of a novel entitled "Batu Manikam". The method used in this research is descriptive qualitative. The results of this study can be concluded that the novel "Batu Manikam" contains cultural values, namely the relationship between man and God, between man and himself, and between man and man, and between man and the environment. In this novel, the cultural values ​​that are more commonly found are cultural values ​​related to human relations with humans, including (1) ridiculing, (2) killing, (3) not having sympathy, (4) lying, (5) betrayal, (6) not holding grudges, (7) conveying the truth, and others. In addition, this study also found its implications for learning Indonesian in high school.